An SIW filtering antenna array with quasi‐elliptic gain response based on intercavity bypass coupling. Issue 3 (18th November 2015) - Chu, Hui; Luo, Sha; Bian, Lei; Guo, Yong‐Xin
ABSTRACT: In this article, a filtering antenna array based on substrate integrated waveguide (SIW) is proposed with quasi‐elliptic gain responses for the first time. Two radiation nulls in the gain responses at two sides of the frequency band edges are designed by applying a novel intercavity bypass coupling scheme. First, by carefully analyzing the bypass coupling between the in‐band and out‐of‐band modes in a single oversized TE103 mode cavity resonator, quasi‐elliptic filtering responses are achieved for a two‐output filter. Afterward, those cavity resonators coupled with the two outputs are replaced by cavity‐backed slot antennas to achieve the proposed filtering cavity‐backed slot antenna array. Only one cavity is required in our design to achieve the two transmission zeros and the function of power divider. As a result, the complexity of the proposed filtering antenna array is reduced. A prototype operating at Ka band is designed, fabricated and measured with a center frequency of 28.5 GHz and fractional bandwidth of 1.25%. Similar characteristics can be observed between the gain response of the proposed filtering antenna and the transmission responses of the two‐output filter. The proposed SIW filtering antenna array has great potential to be integrated into millimeter‐wave transceiver modules. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:191–198, 2016.